Biochar-extracted liquor stimulates nitrogen related gene expression on improving nitrogen utilization in rice seedling - Gao, Jian; Ge, Shaohua; Wang, Hailong; Fang, Yunying; Sun, Luming; He, Tianyi; Cheng, Xiaoyi; Wang, Di; Zhou, Xuanwei; Cai, Heqing; Li, Caibin; Liu, Yanxiang; et al. (Frontiers in Plant Science, 2023)
Biochar can be an effective soil amendment for promoting plant growth and improving nitrogen utilization. However, the physiological and molecular mechanisms behind such stimulating influences remain unclear. Here, we investigated whether biochar-extracted liquor including 21 organic molecules enhance the nitrogen use efficiency (NUE) of rice plants using two nitrogen (N) forms (NH4+-N and NO3--N). In the hydroponic experiment, biochar-extracted liquor (between 1 and 3% by weight) significantly improved phenotypic and physiological traits of rice seedlings. Biochar-extracted liquor dramatically upregulated the expression of rice N metabolism-related genes such as OsAMT1.1, OsGS1.1, and OsGS2. Rice seedlings prefer to absorb NH4+- N than NO3-- N under the treatment of biochar-extracted liquor (p < 0.05). Further, the results from molecular docking showed that OsAMT1.1protein can theoretically interact with 2-Acetyl-5-methylfuran, trans-2,4-Dimethylthiane, S, S-dioxide, 2,2-Diethylacetamide and 1,2-Dimethylaziridine in the biochar-extracted liquor. These four organic compounds have similar biological function as the OsAMT1.1 protein ligand ¬in driving NH4+-N uptakes by rice plants. This study highlights the importance of biochar-extracted liquor in promoting plant growth and nitrogen use efficiency. The use of low doses of biochar-extracted liquor could be an important way to reducing nitrogen input in order to achieve the purpose of reducing fertilizer use and increasing efficiency in agricultural production.